The influence of auditor reputation, firm size, and managerial share ownership on audit report lag - Widyadhana, Keisya Sahda; Oktrivina, Amelia; Ani, Salis Musta (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2024)
This study aims to obtain empirical evidence on the influence of auditor reputation, firm size, and managerial share ownership on audit report lag. The population comprises manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022. Using a purposive sampling method, a final sample of 35 companies was obtained over the three years, yielding 105 data points for observation. The data were analyzed using multiple linear regression with E-views 12. The results indicate that auditor reputation, firm size, and managerial ownership collectively have a significant effect on audit report lag. Specifically, companies audited by Big Four auditors exhibit shorter audit report lags, attributable to their superior resources and technical proficiency. Furthermore, larger firms and those with higher levels of managerial ownership tend to demonstrate more timely audit reporting, which can be linked to stronger internal controls and a greater emphasis on corporate transparency. Article Information:Received 9/1/2024 / Revised 10/8/2024 / Accepted 11/8/2024 / Online First 12/28/2024